Corporate Social Responsibility as part of Public Relations and firm development - Zuzana Lušňáková (Polityki Europejskie, Finanse i Marketing)
The paper deals with Corporate Social Responsibility (CSR) as a part of Public Relation and firm development. We choose one of the most famous fast food all over the world, which is McDonalds company for our research purposes on Corporate Social Responsibility in business firm. The main objective of the article will be to find out, how McDonalds company implements Corporate Social Responsibility towards employees, customers, supply partners, and the community. We also used a questionnaire survey focused on McDonalds employees to find out how does the company implements a corporate social responsibility policy in employee opinion. McDonalds has over 32,000 installations worldwide in 120 countries. McDonalds Slovakia says openly about the social responsibility policy in companys image development and understand CSR as a Public Relation tool in particular, but also as a key tool for society development in accordance to the motto – „if the company thrives, we should feel a commitment to do good.“